The challenges of eradicating informal settlements in South Africa by 2014: the case of Seraleng, Rustenburg Local Municipality, North West Province - Tshikotshi, Victor (My University, 2010)
In 2004, the Department of Housing declared to eradicate informal settlements in South Africa by 2014 following the unprecedented housing backlog, proliferation of informal settlements, social exclusion and the inability of municipalities to provide basic infrastructure to the urban poor households. The domination of the neo-liberal macroeconomic planning policies have also worsened poverty, employment opportunities and increased inequality within the town of Rustenburg. This research report has identified barriers which frequently impact negatively on livelihoods, good governance, security of tenure and sustainability of the affected members of communities. The complexity of informal settlements makes it difficult to relocate residents to greenfield locations. The post-apartheid government’s resettlement programme still locates the urban poor households on the peripheries of the cities, a pattern similar to the one used during the apartheid era. Notwithstanding the acquisition of the individual ownership of the low-cost house, resettled communities still live in abject poverty and risky environmental conditions. In order to respond to the housing problems and poverty, settlement upgrading is mostly appreciated as the necessary mechanism to integrate the fragmented housing sector